Beyond Commercial ERP: A Mixed-Methods Analysis of Challenges and Efficiency Gains from an Internally Developed Kanban System in Pharmaceutical Production - Faiz Ardani, Ahmad; Ratih Hendayani (CITACONOMIA, 2025)
This study examines the implementation and impact of an internally developed ERP-based Kanban system in a pharmaceutical company as a cost-effective alternative to commercial ERP. Utilizing a mixed-methods case study, the research first applied Interpretive Structural Modeling (ISM) to structure key implementation challenges, followed by a quantitative comparative analysis of operational efficiency. Findings reveal a six-level hierarchy of challenges, identifying